Response to conspecific alarm cues by larval and juvenile spotted salamanders (Ambystoma maculatum). Issue 3 (3rd May 2020) - Gardner, Katlyn M.; Hunt, Robert L.; Mathis, Alicia
Abstract : For many species, the highest predation rates are on the earliest life stages, favoring the early development of predator detection mechanisms. Aquatic larvae of Spotted salamanders, Ambystoma maculatum, suffer very high mortality rates and juveniles are vulnerable to a new suite of terrestrial predators after metamorphosis. In some species, adult salamanders assess predation risk via chemical cues released by damaged conspecifics and some heterospecifics ("alarm cues"), but responses of larvae and metamorphs have not been tested. Our first experiment confirmed that field-caught, experienced larvae responded with fright to chemical cues of damaged conspecifics, but not to control cues or alarm cues from toad tadpoles. Responses of sedentary hatchlings in the next experiment indicated that the alarm cue was not present in damaged tissues of hatchlings (1-day-old), but was present by the time the larvae reached the age of 1 month. The third experiment tested responses of naïve lab-reared, free-swimming larvae to alarm cue. In contrast to the other two experiments, these larvae without experience did not distinguish between conspecific alarm cues and control stimuli, suggesting that either embryonic learning or reinforcement learning as larvae may be required to develop or maintain the alarm response. In the fourth experiment, post-metamorphic juveniles raised from field-experienced larvae significantly avoided alarm cues from conspecifics but not control stimuli, indicating that the production and recognition of alarm cues can be retained after metamorphosis. Our study provides the first evidence of chemical alarm cues produced by both larval and juvenile salamanders and indicates that alarm responses may vary according to experience.